2023
DOI: 10.14336/ad.2023.0304
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden among Older COVID-19 Survivors Two Years after Hospital Discharge

Abstract: To study the long-term symptom burden among older COVID-19 survivors 2 years after hospital discharge and identify associated risk factors. The current cohort study included COVID-19 survivors aged 60 years and above, who were discharged between February 12 and April 10, 2020, from two designated hospitals in Wuhan, China. All patients were contacted via telephone and completed a standardized questionnaire assessing self-reported symptoms, the Checklist Individual Strength (CIS)-fatigue subscale, and two subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A possible explanation may be the fear of the high mortality of COVID-19 ( 63 ), which might significantly contribute to an increased risk of developing depressive symptoms. Furthermore, research indicated that individuals who have been hospitalized with COVID-19 are at a high risk of experiencing post-COVID-19 syndrome ( 64 67 ), potentially reflecting poor prognosis which may cause worry and stress among inpatients. Therefore, timely communication with patients about their health status and progress of treatment is necessary to alleviate their fear of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation may be the fear of the high mortality of COVID-19 ( 63 ), which might significantly contribute to an increased risk of developing depressive symptoms. Furthermore, research indicated that individuals who have been hospitalized with COVID-19 are at a high risk of experiencing post-COVID-19 syndrome ( 64 67 ), potentially reflecting poor prognosis which may cause worry and stress among inpatients. Therefore, timely communication with patients about their health status and progress of treatment is necessary to alleviate their fear of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…1 We attempted to identify new eligible studies that reported the incidence of post-COVID fatigue 2 years after COVID-19 infection. Finally, nine new studies were identified, four from Asian countries [2][3][4][5] and five from non-Asian countries. [6][7][8][9][10] We pooled these data from the new studies with 10 studies in the original meta-analysis 1 using Comprehensive Meta-Analysis software (Version 4, Biostat).…”
mentioning
confidence: 99%